Industrialization And Blockchain Strategy In Supporting The Achievement Of SDG's And Food Security: A Case Study Of The Fisheries Industry Supply Chain With SEM, AHP, OR, and Spatial Analysis Approaches (East Java, Ambon, Makassar, Madura) - Prananta, Arie; Wardhana, Indra; Away; Mahfudz, Iqbal (Journal Management & Economics Review (JUMPER), 2025)
This study investigates strategies for integrating blockchain technology into Indonesia’s capture fisheries supply chain to enhance transparency, operational efficiency, and sustainability, thereby contributing to the achievement of Sustainable Development Goals (SDGs) 2, 12, and 14. Employing a mixed-methods approach, the research combines Structural Equation Modeling (SEM), Analytic Hierarchy Process (AHP), Operational Research (goal programming), and Geographic Information System (GIS)-based spatial analysis. Data from 210 fisheries stakeholders were analyzed to identify determinants of blockchain adoption, prioritize strategic criteria, and optimize policy objectives. The SEM results (R² = 0.67) indicate that government support and perceptions of transparency significantly influence adoption intention. AHP prioritization highlights data transparency and accuracy (0.34) as the most critical criterion, followed by infrastructure readiness (0.27), capacity development (0.23), and cost efficiency (0.16). Goal programming optimization recommends a strategic combination of logistics traceability, digital training, and certification systems, while spatial analysis identifies Makassar, the North Coast of East Java, and Ambon as priority zones for implementation. The findings underscore that blockchain adoption in the fisheries sector is not solely a technological intervention but a systemic transformation requiring institutional reform, infrastructure investment, and multi-stakeholder collaboration. The study provides an evidence-based roadmap for place-based blockchain deployment, aiming to improve fisheries governance and strengthen Indonesia’s competitiveness in global seafood markets.